HIDUP BERSIH DAN SEHAT DENGAN PROGRAM JAMBANISASI - Olifiani Nurul Malida; Ilfa Nihlatika; Novi Indah Lestari; Ahmad Fauzan Hidayatullah (J-KESMAS: Jurnal Kesehatan Masyarakat, 2020)
Clean and healthy environmental conditions greatly affect the health of the community such as the provision of clean water, latrines in every family, and environmental conditions around the house. This study aims to find out how to live clean and healthy with a latrine program. Through a latrine program it will increase awareness of the negative effects of open defecation. This condition has greatly reduced sanitation in the surrounding environment. This research method uses the literature review method. To maintain accuracy of the assessment and prevent misinformation in data analysis, checking is done between libraries and rereading the libraries. The results of this study are there are still some people who have an attitude that does not agree even do not agree to use the toilet, do not have a toilet, so it does not rule out the transmission of various diseases will occur.